Religion, Disability, and Sustainable Development in Africa - Chioma Ohajunwa; Kudakwashe ‘AK’ Dube; Ezra Chitando (Routledge, 2025)
This book investigates the interplay between disability and religion in Africa, and what this means in the context of the Sustainable Development Goals.The importance of meeting the needs of people with disabilities is highlighted specifically in several Sustainable Development Goals, as well as being emphasised as a cross-cutting issue across all the goals. Over 1 billion people are estimated to be living with disabilities, and 80% of this population live in the Global South, many within Africa. This book argues that within this context, religion must be considered, as people with disabilities often turn to religion for solace in confronting the daily struggles and pains that they face. Drawing on multiple disciplinary lenses, this book reflects on how traditional/indigenous, Abrahamic, and other African minority religions and philosophies interact with disability, and how this relates to the Sustainable Development Goals. The book demonstrates how religions in Africa conceptualise, imagine, or re-imagine disability in the context of key themes such as gender, ecological justice, health, poverty, education, employment, entrepreneurship, and migration.Overall, the book invites researchers from across the social sciences to consider how African religious, theological, and philosophical ideas can help towards the inclusion of people with disabilities in the 2030 development agenda in Africa.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available by KU 2025 under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.